Glycemic control, including Time in Tight Range (TITR) evaluation, in children with type 1 diabetes treated with the MiniMed 780G system: a 3-year prospective, observational, two-center study - Tarasiewicz, Mateusz; Bartnikowska, Wiktoria; Chobot, Agata; Bielawska, Anna; Zając, Agnieszka; Polańska, Joanna; Jarosz-Chobot, Przemysława; Seget, Sebastian (Frontiers in Endocrinology, 2026)
BackgroundThe MiniMed 780G was the first commercially available automated insulin delivery (AID) system in Poland. The aim of this study was to analyze glycemic management in children with type 1 diabetes (T1D) after three years of using the system.Materials and methodsThe data included anthropometric measurements, information from insulin pumps, and continuous glucose monitoring (CGM) from fifty children with T1D (mean age: 9.9 ± 2.4 years; T1D duration at baseline: 3.9 ± 2.56 years) using the MiniMed 780G. The data were collected at AID initiation, 12 and 36 months after starting its use.ResultsCoefficient of variation (CV) and body mass index (BMI) z-scores at baseline and after 3 years were comparable (p > 0.05). TITR firstly increased after the AID system implementation with the peak value after 6 months (60.82% ± 9.34), then the values decreased to 56.50%± 10.78% after 3 years (p<0.001). Time in range (70–180 mg/dL) decreased after 3 years of observation compared to peak values at 6 and 12 months (77.74% ± 7.65% versus 81.16% ± 7.83% and 80.40% ± 8.25%, respectively, p<0.005. The percentage of auto-correction in total daily insulin dose increased significantly (11.24% ± 6.08% 2 weeks of AID system usage vs. 16.34% ± 6.69% after 3 years; p < 0.001).ConclusionsDespite a slight deterioration after 3 years, optimal glycemic management was maintained throughout the observation period. GCM metrics remained within recommended values in early adolescence, most likely due to auto-correction boluses.